2005
DOI: 10.1111/j.1538-7836.2005.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

A new signaling mechanism of hepatocyte growth factor‐induced endothelial proliferation

Abstract: Summary. Background: The hepatocyte growth factor (HGF) has been shown to promote endothelial cell proliferation. In this study, the signaling cascade responsible for the HGF-induced proliferation was examined. Methods: The proliferation of human umbilical cord vein endothelial cells (HUCVEC) was determined using cell counts. Changes of the membrane potential were analyzed using the fluorescence dye DiBAC. Intracellular cGMP-levels were measured by means of [ ). A HGF-induced hyperpolarization that was blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…It has been reported that EGFR and c-Met are involved in cell migration (20,(35)(36)(37)(38). In the present study, we showed that migration of the OSCC cell lines SAS and Ca9-22 was regulated by both the EGFR and c-Met signalling pathways.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that EGFR and c-Met are involved in cell migration (20,(35)(36)(37)(38). In the present study, we showed that migration of the OSCC cell lines SAS and Ca9-22 was regulated by both the EGFR and c-Met signalling pathways.…”
Section: Discussionsupporting
confidence: 56%
“…Because HGF-induced MAP kinase cascade activation had been demonstrated to trigger a proliferation response in other brain regions (Ieraci et al, 2002;Kuhlmann et al, 2005), the . HGF is a chemoattractant for RMS neuroblasts.…”
Section: Metmentioning
confidence: 99%
“…HGF, also known as scatter factor, is the natural ligand for the receptor tyrosine kinase, c-Met (6) that is expressed on a variety of cell types including vascular endothelial cells and is up-regulated during angiogenesis (7,8). HGF interacts with its cognate receptor c-Met and promotes angiogenesis by enhancing the expression of vascular endothelial growth factor, one of the principal mediators of angiogenesis.…”
mentioning
confidence: 99%
“…HGF interacts with its cognate receptor c-Met and promotes angiogenesis by enhancing the expression of vascular endothelial growth factor, one of the principal mediators of angiogenesis. HGF binding to c-Met triggers a cascade of signal transduction pathways including activation of phosphatidylinositol 3-kinase (PI3k) and Akt, which have been implicated in cell migration (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation